IMPLEMENTASI LAYANAN BIMBINGAN KONSELING DALAM MEWUJUDKAN KESEJAHTERAAN PSIKOLOGIS SISWA DI SMPIT AN-NIDA - Seprianto, Seprianto; Fadila, Fadila; Ristianti, Dina Hajja; Azwar, Beni (MUHAFADZAH: Jurnal Ilmiah Bimbingan dan Konseling Islam, 2024)
Psychological well-being of adolescents is an important concern in the context of today's globalization, including in Indonesia, where social changes, technology, and complex life demands have the potential to affect their psychological well-being. This study aims to investigate the implementation of guidance and counseling services at SMPIT An-Nida' in Lubuklinggau City in achieving students' psychological well-being. This study uses a field research approach with a qualitative approach. Primary data were collected through observation, interviews, and documentation at SMPIT An-Nida'. Secondary data include information related to school policies and documentation of student activities. The profile of students' psychological well-being at SMPIT An-Nida' shows that the majority of students have high levels of joy and life satisfaction. However, some students face challenges related to academic and social stress. The implementation of guidance and counseling services is effective in improving psychological well-being, with a holistic approach that includes individual and group services and self-development strategies. Kesejahteraan psikologis remaja menjadi perhatian penting dalam konteks globalisasi saat ini, termasuk di Indonesia, di mana perubahan sosial, teknologi, dan tuntutan hidup kompleks berpotensi memengaruhi kesejahteraan psikologis mereka. Penelitian ini bertujuan untuk menginvestigasi implementasi layanan bimbingan konseling di SMPIT An-Nida' Kota Lubuklinggau dalam mencapai kesejahteraan psikologis siswa. Penelitian ini menggunakan pendekatan field research dengan pendekatan kualitatif. Data primer dikumpulkan melalui observasi, wawancara, dan dokumentasi di SMPIT An-Nida'. Data sekunder meliputi informasi terkait kebijakan sekolah dan dokumentasi aktivitas siswa. Profil kesejahteraan psikologis siswa di SMPIT An-Nida' menunjukkan mayoritas siswa memiliki keceriaan dan kepuasan hidup yang tinggi. Meskipun demikian, beberapa siswa menghadapi tantangan terkait stres akademik dan sosial. Implementasi layanan bimbingan konseling efektif dalam meningkatkan kesejahteraan psikologis, dengan pendekatan holistik yang mencakup layanan individu dan kelompok serta strategi pengembangan diri.